State capacity and the resilience of electoral authoritarianism: Conceptualizing and measuring the institutional underpinnings of autocratic power. Issue 1 (January 2018) - Hanson, Jonathan K
This article discusses three main challenges to gaining a better understanding of whether state capacity contributes to the resilience of electoral authoritarian regimes. First, the concept of state capacity is multi-dimensional and can be entangled with regime organizational structures. Second, there is a range of different mechanisms through which elections may draw upon capacity in these different dimensions to affect authoritarian resilience. Third, good indicators of the dimensions of state capacity for empirical work are sorely lacking. To address these challenges, this article outlines the connections between extractive, coercive and administrative dimensions of state capacity with regard to how electoral authoritarian regimes address threats arising from society and from within the ruling elite. It then assesses different approaches to measuring these dimensions for empirical work.